A nationwide prospective registry of bortezomib-based therapy in light chain (AL) amyloidosis. Issue 1 (2nd January 2022) - Palladini, Giovanni; Celant, Simone; Milani, Paolo; Summa, Valentina; Affronti, Giovanni; Olimpieri, Pier Paolo; Petraglia, Sandra; Foli, Andrea; Nuvolone, Mario; Merlini, Giampaolo; Russo, Pierluigi
Abstract: Until recently, no drug was labeled for AL amyloidosis. In 2011, the Italian Medicines Agency started a program to grant access to upfront bortezomib to patients with AL amyloidosis. All subjects were enrolled in a prospective online registry. Response was evaluated after two cycles to assess the possibility of continuing treatment. A total of 764 patients were included until 2019, and 615 were evaluable. Sixteen percent of patents had advanced (stage-IIIb) heart involvement, and 27% had severe or end-stage renal failure. Bortezomib delivery was possible in stage-IIIb patients at a reduced dose. Bortezomib discontinuation was associated with increasing age, advanced heart involvement and bi-weekly administration. Fifty-nine percent of subjects attained a hematologic response and 14% a cardiac response. Bortezomib-based therapy tends to be discontinued early in elderly patients and in advanced disease. Nevertheless, early response to therapy is possible in this challenging population.